Rethinking Multimodal Literacy in Theory and Practice - Domínguez Romero, Elena; Bobkina, Jelena; Stefanova Radoulska, Svetlana; Herrero, Carmen (Peter Lang, 2024)
The wide range of scholarly works in fields of enquiry such as film and media studies, cultural studies, linguistics, and education demonstrates the exponentially expanding interest in multimodality over the past two decades (see, e.g., Bateman & Schmidt, 2012; Djonov & Zhao, 2014; Kress et al., 2014). The creation of a new SAGE journal, Multimodality & Society, whose first issue was published in 2021, testifies to the growing body of literature on multimodality. Multimodal methodologies, based on Gunther Kress’s idea that “language, whether as speech or as writing, is one as many available for representation and for making meaning” (2012, p. 37), have gained in popularity, showing beyond doubt the relevance of different theoretical perspectives and their practical application in the classroom. Unlike traditional studies in foreign language teaching, which focus mainly on language, in multimodal approaches language is just one of the multiple modes for meaning-making and communication. Although studies show that “multimodal resources integrate naturally to facilitate language teaching and learning in an orderly, structured and goal-oriented manner in classroom lessons” (Tan et al., 2016, p. 253), the multimodal turn reveals the need to integrate the development of multiliteracies in our understanding of effective communication. The changing nature of learning environments, which involve rapidly evolving digital practices and media affordances, renders certain conventional approaches obsolete and requires greater flexibility and faster adaptability of the teaching process to the new multi-semiotic and multisensory virtual learning environments.
Keywords: multimodal; language; innovations; teachers; Scopus